Carbon and nitrogen status of decomposing roots in three adjacent coniferous plantations - Jaeyeob Jeong; Choonsig Kim (Annals of Forest Research, 2014)
This study evaluated the carbon (C) and nitrogen (N) status of decomposing roots in three adjacent plantations consisting of one deciduous (larch: Larix leptolepis) and two evergreen (red pine: Pinus densiflora; rigitaeda pine: P. rigitaeda) species planted in the same year (1963) under similar site conditions. The mass loss rates and C and N status of three diameter classes of roots (UF < 2 mm, F 2-5 mm, CF 5-10 mm in diameter) were examined in the upper 15 cm of the mineral soil using in situ buried root bags for 496 days.The remaining mass of decomposing roots was significantly higher for larch (69.0%) than for red pine (59.6%) or rigitaeda pine (59.1%) over 496 days. The mass loss rates of decomposing roots did not differ significantly among the three root diameter classes, but the C and N status of decomposing roots was affected by the tree species. The larch roots showed low C concentrations but high N concentrations, C and N remaining compared to the pine roots over the study period. The results indicate that the substrate quality indicators of roots were not attributed to the mass loss rates, C and N status of decomposing roots in three coniferous tree species grown under similar environmental conditions.